Investigation of the Geothermal Potential of Mount Seminung, West Lampung, Indonesia, Based on Magnetic Anomaly Data - Ellin Ernita Mahdalya; Muchammad Farid; Refrizon Refrizon; Hana Raihana (Diponegoro University Semarang Indonesia, 2026)
Indonesia has significant geothermal potential due to its location along the active tectonic Ring of Fire, characterized by intense volcanic activity and fault structures. One promising area is Mount Seminung in Sukau District, located in the southeastern part of the Ranau Caldera and influenced by the Sumatra Fault system. This study aims to analyze the distribution of magnetic anomalies as an initial indication of a geothermal system in the Mount Seminung area. The study employed the magnetic method by measuring total magnetic field intensity at several observation points across the study area using a proton precession magnetometer. The magnetic data were corrected for diurnal variations and the Earth's main magnetic field, then processed to produce a magnetic anomaly map. The results show low magnetic anomaly zones ranging from −374.2 nT to −9.0 nT, which are associated with hydrothermal alteration and geothermal manifestations, and high anomaly zones ranging from 181.5 nT to 871 nT related to relatively fresh volcanic rocks. The anomaly contrasts and elongated gradient patterns indicate the presence of faults or fractures that may act as pathways for geothermal fluids. Therefore, the low anomaly zones associated with these structures are recommended as targets for further investigation using geoelectric or magnetotelluric methods.